Mobilizing Home: Diasporic Agitations and the Global Remakings of Postwar Southeastern Nigeria. (4th March 2022) - Lu, Vivian Chenxue
Abstract: In the context of shifting global geographies of labor and political volatility, Nigerian migrant associations play a significant role in organizing diasporic life. Yet, far from being a culturally static feature, Igbo Nigerian associations emerge through diasporic agitations, or dynamic mobilizations around particular events, crises, and projects that deliberately engage the postcolonial state. Lu first reconsiders the significance of 1970s post-civil war reconstruction in southeastern Nigeria before tracing subsequent transformations in flexible diasporic organizations within Global South locations such as China and Dubai. These agile and multi-scalar diasporic mobilizations enable their members to negotiate the nexus of postcolonial politics and transnational capitalism.